The development of car seat alert system through telegram application - Samsudin, Adam; Abd Razak, Khairool Aizat; Jaffar, Kamilah; Salim, Fadzilah; Razali, Mohd. Aminudin; Mohd. Ali, Mohamad Aiman; Azmi, Ezzatul Farhain (Asian Research Publishing Network (ARPN), 2022)
This paper discusses the development of a car seat alert system through telegram application to design and develop a car seat alert system for babies that have been left in vehicles and get heatstroke deaths. This type of accident is called vehicular heatstroke and it is very dangerous to a baby because their body overheats 3-5 times faster than an adult body. Plus, the inside of a vehicle is heating up very quickly and it very concerns parents to bring their child to travel using car. Nowadays, heatstroke deaths of children in vehicles are quite encouraging and every year the number of cases is increasing. In an overwhelming majority of child vehicular heatstroke deaths, it was loving, responsible parents that unknowingly left the child. This project was created to inform and alert the parents out there when they might forget their child is left under any circumstances. To make sure this project system is more practical, NodeMCU is used as a microcontroller to control all the input and output devices in this system. As to alert parents when this carelessness is happening the LED and Buzzer are provided in this system. Apart from that, LCD is used to display the presence of the child at the seat and temperature value inside. GPS module is used to give the location to inform the driver that the child was been left in the car. As to ensure the goals stated will be achieved, significant research has been made thoroughly that will act as references throughout these studies for this project